Sharia financial in cross civilization and humanity: a study of alternative solutions to the economy - Septi Vivia Nur Baiti; Shovia Indah Firgianti; Ahmad Lukman Nugraha (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
This article aims to identify views on usury in various perspectives and identify problems with usury and identify solutions. Usury in various perspectives is a cause of problems in the economy, which also refers to humanitarian issues globally. Learning about solutions to eliminate usury in the economy is a study that is developing, so that this is part of the development of civilization towards an economy that is growing and developing. Islamic economics and finance is a solution to build a humanitarian and civilized economy.